Identification of Sugarcane S. spontaneum (Poaceae) Germplasm: Evidence from rDNA-ITS and rDNA Locus Analyses - Pingping Lin; Xuguang Hu; Li Xue; Xinyi Li; Ping Wang; Xinwang Zhao; Muqing Zhang; Zuhu Deng; Fan Yu (Agronomy, 2022)
Sugarcane is a major crop for sugar production around the world. The complexity of the sugarcane genome creates challenges for the use of both conventional and molecular breeding methods to improve sugarcane at a genetic level. DNA sequencing is an important tool to assess how the genus Saccharum and the genera of the Saccharum complex are interrelated. Here, we identify the kinship of Nepal2013-6 (Saccharum spontaneum, x = 10) using a tetra-primer amplification refractory mutation system (ARMS) PCR. Based on rDNA-ITS sequence analysis, the accession Nepal2013-6 falls within a single cluster with S. spontaneum (Yunnan82-114 and SES208), which is consistent with the previous results. Moreover, fluorescence in situ hybridization (FISH) results indicate that the 5S rDNA spots are consistent with the chromosomal ploidy in the analytical Saccharum materials, whereas 35S rDNA has similar or fewer sites than the ploidy. Therefore, 5S rDNA FISH patterns would be more suitable than 35S rDNA for chromosomal ploidy analysis in S. spontaneum with varied basic chromosome number x = 8, 9, 10. Altogether, these results indicate that the rDNA sequences will be a useful marker for further rapidly identifying the relationship and ploidy of S. spontaneum in sugarcane breeding.